Enhancing humanities and social sciences curriculum in engineering institutions by using interdisciplinary approaches - Minhui Li; Xu Liu (Cogent Education)
High-quality humanities and social sciences (HSS) courses tailored to Science, Technology, Engineering, and Mathematics (STEM) students have become a crucial platform for expanding their thinking and communication abilities, as well as fostering humanistic awareness. This research explores the approaches employed by interdisciplinary HSS courses for STEM students and explores how these HSS courses cultivate the critical thinking, innovative capabilities, and social awareness of these students. It examines the integration of HSS courses into education of STEM. Of the 400 HSS courses offered, it examines 20, all rated by students as in the top 15%, and explores their different approaches to cultivating critical thinking, innovative capabilities, and social awareness in STEM students. Through research, it identifies three key findings: the process of student self-construction encompassing knowledge, skills, and literacy; the multifaceted role of HSS courses instructors as messengers, facilitators, and advisors; and the implementation of diverse evaluation strategies, including open-ended, non-standard, and peer-review methods. These findings underscore the significance of interdisciplinary HSS courses in fostering engineers’ social responsibility, humanistic literacy, and broad cognitive abilities. The study advocates for a holistic engineering education that integrates humanistic values and interdisciplinary knowledge.